2013
DOI: 10.1177/0954409713497199
|View full text |Cite
|
Sign up to set email alerts
|

Twin-tube- and bypass-containing magneto-rheological damper for use in railway vehicles

Abstract: A 9-kN magneto-rheological (MR) damper for lateral suspension control of a railway vehicle is created in this paper. The twin-tube style is adopted in order to obtain a long damper stroke and guarantee the symmetry of the output damping force. A bypass MR valve with a radial flow path is utilised to control the generated damping force. Three-dimensional finite element analysis studies are performed to determine the magnetic field strength inside the MR valve region. The MR damper is mathematically modelled for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Only adopting onestage radial flow mode, this damper obtains relatively large damping force. e experimental results have demonstrated that the damping force is up to 9 kN under an exciting current of 1.6 A [28].…”
Section: Radial Channels Controlled By Magnetic Fieldmentioning
confidence: 98%
See 2 more Smart Citations
“…Only adopting onestage radial flow mode, this damper obtains relatively large damping force. e experimental results have demonstrated that the damping force is up to 9 kN under an exciting current of 1.6 A [28].…”
Section: Radial Channels Controlled By Magnetic Fieldmentioning
confidence: 98%
“…Still considering the advantages of a radial flow mode and a bypass valve, a damper in a suspension system of a high-speed train had been designed by Guo et al, shown in Figure 36 [28,93]. One-way valves in a piston and the foot valve are helpful to form a flow along a single direction.…”
Section: Radial Channels Controlled By Magnetic Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…The properties of MR damper can be changed by changing applied current [1]. MR damper have been chosen over a decade for vehicle suspension system [2][3][4], helicopters seat [5], civil structure base isolation [6][7][8], and railway transport [9,10]. Semi-active MR damper is especially applicable for unpredictable motion conditions and capable large payload condition.…”
Section: Introductionmentioning
confidence: 99%
“…MR fluids are attractive because they provide a simple and rapid response interface between electronic controls and mechanical systems. MR damper is used in automotive industry (Nguyen, 2009), for the control of seismic vibrations in buildings (Yang, 2002), in railway industry (Guo, 2014) or for damping in stay cable bridges (Choi, 2007). MR damper provides high force dynamic range, is reliable and has low energy consumption (Yang, 2002).…”
Section: Introductionmentioning
confidence: 99%